Understanding digitally mediated civic engagement for infectious disease preparedness - Panchapakesan Kumari Chitra (2019)
Infectious diseases have tremendous impact on the society. It is a complex health problem that poses a massive challenge in identifying solutions to tackle it effectively. Researchers feel that digitally mediated civic engagement (DMCE), which is a fast-developing field of research within health communication, can potentially help to enhance the health of a community (Boulos et al., 2011). DMCE makes the system faster and efficient by acting as proper bridge between the authorities and the public. The general public could reporting incidents, ask doubts and health authorities can respond to it without time delay. However, the motivators behind individuals’ attitude towards and use of digitally mediated civic engagement for health communication are under studied. The major contribution of this Ph.D thesis is to understand the DMCE drivers in the context of infectious diseases based on grounded theory, protection motivation theory and social capital elements. Dengue has been selected for studying the effect of DMCE, as it is a major health problem, especially in tropical countries such as Singapore, India and Sri Lanka (MOH, 2013, 2014a; Halasa, 2011; Epidemiology Unit, 2017). This thesis has three main objectives: first, to understand the public’s view, use and motivators of DMCE; second, to develop and assess a conceptual model to understand the key factors driving DMCE and third, to understand how digital media designers, medical professionals and developers view strategies that enable DMCE. A series of studies were undertaken to meet these objectives. First, a preliminary study is undertaken to provide a detailed understanding of general public’s opinions and views towards DMCE. This study also provides an in-depth knowledge of the motivating factors and barriers of DMCE. Using the results from this study and existing literature, a second study is planned and executed. A conceptual model is developed based on protection motivation theory and social capital elements to explain the motivators of DMCE, which is tested with a survey study in two countries- India and Singapore. The results of the study show the significant influence that individuals' social capital, beliefs towards disease protection such as self-efficacy and response efficacy, media use, etc., have on their DMCE. Finally, it is vital to understand and examine the facets that are being considered by developers and health authorities in encouraging DMCE in health communication applications behind the app development process. This is the bedrock of the researcher’s third study, which was conducted during an international workshop that brought health and IT professionals together to develop health communication apps for DMCE. Another key outcome of this final piece of research was the identification of other factors that need to be weighed in is the understanding the successful utilization of the tools for health interventions. A significant contribution of this research is in the understanding of DMCE for infectious disease preparedness in the Asian context. This work is one of the first attempts to construct a conceptual model combining PMT variables with social capital elements to understand the motivators of DMCE in health communication context based on empirical findings and previous literature. The study also provides insights into the factors that are considered by the health developers and authorities while developing health application for encouraging public participation. The findings resulting from this body of research will be valuable in the design of social marketing strategies, educational interventions and framing health messages to motivate public to take part in DMCE.